Method for synergistically mineralizing bacteria by cerium phosphate and cerium oxide and application of high-acid-resistant and antioxidant probiotics

CN122461262BActive Publication Date: 2026-09-22SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610911684.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-09-22
Estimated Expiration
2046-06-24

AI Technical Summary

Technical Problem

[0006]本发明的首要目的在于克服现有技术的缺点与不足,提供一种通过在细菌表面原位矿化生成具有致密的、具有多尺度纳米结构的含铈纳米壳层(铈的氧化物与磷酸盐复合物),解决现有益生菌耐酸性差、易被氧化失活的问题,同时拓宽该益生菌的应用范围

Benefits of technology

1. 本发明所得复合矿化益生菌不仅在模拟胃液条件下存活率提升至近90%,还可明显降低DPPH自由基、ABTS自由基,有效提高了益生菌口服递送后在胃肠道中的存活率,并强化了益生菌的口服递送治疗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122461262B_ABST
    Figure CN122461262B_ABST
Patent Text Reader

Abstract

The application discloses a method for synergistically mineralizing bacteria by cerium phosphate and cerium oxide and high-acid-resistant and antioxidant probiotics and application, and the method generates a compact cerium-containing nanoshell layer with a multi-scale nano structure on the surface of bacteria in situ mineralization, wherein the nanoshell layer contains cerium oxide and phosphate compounds simultaneously; the physical barrier effect of the cerium-containing nanoshell layer and the valence state conversion characteristics of cerium endow the probiotics with high acid resistance and antioxidant capacity. The survival rate of the bacteria mineralized by the cerium phosphate and cerium oxide constructed by the application is significantly improved under acidic environment and oxidative stress conditions, the technical problem that the probiotics are prone to inactivation during production, storage and in-vivo transportation is solved, the survival rate of the probiotics is effectively improved, and then as many live bacteria as possible can reach the target position and play a role during application of the probiotics, and the utilization rate of the probiotics is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of microbial engineering and nanomaterials application technology, and in particular to a method for synergistic mineralizing bacteria of cerium phosphate and cerium oxide, as well as highly acid-resistant and antioxidant probiotics and their applications. Background Technology

[0002] Probiotics are a class of live microorganisms that are beneficial to the host, regulating the balance of intestinal flora, enhancing immune function, and improving metabolic health. The beneficial effects of probiotics are widely recognized; however, their practical application faces several challenges. Firstly, after entering the human body, probiotics must pass through the acidic environment of the stomach (pH 1.5-3.5), where acidic conditions can damage their cell membrane structure, leading to significant inactivation. Secondly, oxidative stress substances such as reactive oxygen species present in the intestines can damage the DNA and proteins of probiotics, reducing their biological activity. Furthermore, probiotics are easily inactivated by factors such as acidity, alkaliness, and oxidation during production, processing (e.g., high-temperature drying), and storage, severely limiting their effectiveness.

[0003] To address the aforementioned issues, existing technologies often employ microencapsulation techniques, using biomolecules such as polysaccharides and proteins as encapsulation materials. However, these materials have limited acid resistance and antioxidant properties, making it difficult to effectively protect probiotics.

[0004] Existing technologies use polydopamine to protect probiotics from damage by gastric acid and digestive enzymes. However, the oxidative polymerization mechanism of dopamine poses a challenge to the stringent survival conditions required by probiotics. Traditional reactions (involving strong oxidants and strong ultraviolet radiation) are not suitable for probiotic surface modification. Based on this, the existing technology "A Nanoenzyme Coating Modified Probiotic and Its Preparation Method and Application" uses metformin to provide mild reaction conditions and maintain probiotic activity. At the same time, it combines nanoenzymes (such as cerium dioxide, iron tetroxide, and iron single-atom nanoenzymes) to assist in the oxidative polymerization of dopamine, decomposes reactive oxygen species at the site of intestinal inflammation, and utilizes MET to promote the transformation of intestinal macrophages into anti-inflammatory M2 types, among other mechanisms, to achieve the inflammation-targeting clearance function of the coating-modified probiotics. However, while this technology, which "uses polydopamine to protect probiotics from damage by stomach acid and digestive enzymes, and adds metformin to utilize its antioxidant effect to prevent damage to probiotics during the dopamine polymerization process," has improved the maintenance of probiotic activity to some extent, it is still far from sufficient, and the survival rate of probiotics is less than 10% (from 10...). 8 CFUs dropped to less than 10 7 CFUs).

[0005] Therefore, how to effectively improve the survival rate of probiotics so that enough live bacteria can reach the target location and play a role during use remains a problem that urgently needs to be solved. Summary of the Invention

[0006] The primary objective of this invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method that generates a dense, multi-scale nanostructured cerium-containing nanoshell (a complex of cerium oxide and phosphate) on the surface of bacteria through in-situ mineralization. This method addresses the problems of poor acid resistance and easy oxidation and inactivation of existing probiotics, while also broadening the application scope of the probiotic.

[0007] A second objective of this invention is to provide highly acid-resistant and antioxidant probiotics obtained by the above method.

[0008] A third objective of this invention is to provide the application of the above-mentioned highly acid-resistant and antioxidant probiotics.

[0009] The objective of this invention is achieved through the following technical solution: A method for synergistic mineralizing bacteria of cerium phosphate and cerium oxide includes the following steps: S1. Add cerium ions and phosphate to the bacterial solution so that the final concentration of cerium ions in the bacterial solution is 0.1-100 mmol / L and the final concentration of phosphate in the bacterial solution is 0.1-100 mmol / L; S2. The reaction is carried out at a pH of 3.5–9.0 and a temperature of 10–60℃ for 0.5–24 h to obtain the mineralized bacterial solution after reaction and mineralization.

[0010] Alternatively, after the reaction, the mineralized bacterial cells can be centrifuged, separated, and washed to obtain mineralized bacteria.

[0011] Furthermore, the bacterial solution mentioned in S1 is a probiotic bacterial solution.

[0012] Furthermore, the probiotics include at least one of non-pathogenic Escherichia coli, Lactobacillus rhamnosus, Lactobacillus plantarum, Bifidobacterium longum, Bifidobacterium bifidum, and Bacillus subtilis.

[0013] Furthermore, the probiotic mentioned is Escherichia coli Nissle 1917.

[0014] Furthermore, the addition of cerium ions and phosphate ions as described in S1 is as follows: first, add a reagent containing cerium ions, stir and adsorb for 5 to 60 minutes, and then add a reagent containing phosphate ions. The cerium-containing reagents include soluble cerium salts; The phosphate-containing reagents include at least one of soluble inorganic phosphates and soluble organic phosphates.

[0015] Furthermore, the soluble cerium salt includes at least one of cerium nitrate, cerium chloride, or cerium acetate.

[0016] Furthermore, the soluble cerium salt is cerium nitrate.

[0017] Among them, cerium ions in soluble cerium salts preferentially adsorb onto carboxyl, hydroxyl, phosphate, or amino sites on the bacterial surface.

[0018] Furthermore, the phosphate-containing reagent is a soluble inorganic phosphate.

[0019] Furthermore, the soluble inorganic phosphate includes at least one of sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate.

[0020] Furthermore, the soluble inorganic phosphate is sodium dihydrogen phosphate.

[0021] Furthermore, the concentration of the bacterial solution described in S1 is 1×10⁻⁶. 7 ~1×10 11 CFU / mL.

[0022] Furthermore, the concentration of the bacterial solution is 1×10⁻⁶. 8 ~1×10 10 CFU / mL.

[0023] Furthermore, the concentration of the bacterial solution is 1×10⁻⁶. 9 CFU / mL.

[0024] Furthermore, the final concentration of cerium ions in the bacterial culture as described in S1 is 1–30 mmol / L.

[0025] Furthermore, the final concentration of cerium ions in the bacterial solution is 10 mmol / L.

[0026] Furthermore, the final concentration of phosphate in the bacterial culture as described in S1 is 1–100 mmol / L.

[0027] Furthermore, the final concentration of phosphate in the bacterial culture is 20 mmol / L. Furthermore, the ratio of bacteria, cerium ions, and phosphate in the bacterial solution described in S1 is 1×10⁻⁶. 9 ~1×10 13 CFU: 1 mmol: 0.01~200 mmol.

[0028] Furthermore, the ratio of bacteria, cerium ions, and phosphate in the bacterial solution is 1×10⁻⁶. 9 ~1×10 13 CFU: 1mmol: 0.67~20 mmol.

[0029] Furthermore, the ratio of bacteria, cerium ions, and phosphate ions in the bacterial solution is 1×10⁻⁶. 11 ~1×1013 CFU: 1 mmol: 0.67~5 mmol.

[0030] Furthermore, the ratio of bacteria, cerium ions, and phosphate ions in the bacterial solution is 1×10⁻⁶. 11 ~1×10 13 CFU: 1 mmol: 2-5 mmol.

[0031] Furthermore, the ratio of bacteria, cerium ions, and phosphate in the bacterial solution is 1×10⁻⁶. 11 CFU: 1 mmol: 2 mmol.

[0032] Furthermore, the pH value described in S2 is 4.5–7.5; The temperature is 20–45°C; The reaction is carried out over a period of 1 to 24 hours.

[0033] Furthermore, the pH is 6.0.

[0034] Furthermore, the temperature is 35°C.

[0035] Furthermore, the reaction is carried out for 6 to 24 hours.

[0036] Furthermore, the reaction is carried out for 6 hours.

[0037] Furthermore, the average particle size of the composite nanoshell of the mineralizing bacteria is 5–300 nm, preferably 10–150 nm; the average thickness of the shell is 5–200 nm, preferably 10–80 nm.

[0038] In the reaction process described above, a portion of the cerium ion component reacts with phosphate to form cerium phosphate, while another portion of the cerium ion component forms cerium oxide under the influence of dissolved oxygen, active groups on the bacterial surface, and / or oxidative conditions, thereby synergistically constructing a cerium phosphate / cerium oxide composite nanoshell on the bacterial surface.

[0039] The cerium phosphate / cerium oxide composite nanoshell contains both CePO4 and CeO2, with CeO2 serving to provide reversible Ce. 3+ / Ce 4+ The reactive oxygen species scavenging capacity mediated by the cycle, but the Ce provided by it 3+ / Ce 4+ The proportion is relatively low, while CePO4 can not only provide Ce 3+ Used to enhance Ce 3+ / Ce 4+ It can also be used to enhance acid resistance and interfacial stability, and the two work together to enable probiotics to maintain higher activity in gastrointestinal stress and inflammatory microenvironment.

[0040] Furthermore, the mineralized bacteria can be further processed by freeze drying, spray drying, fluidized bed granulation, or enteric solvent processing to obtain a compound mineralized probiotic preparation.

[0041] A highly acid-resistant and antioxidant probiotic was prepared by the above-mentioned method of cerium phosphate and cerium oxide synergistic mineralizing bacteria.

[0042] This invention also claims protection for the use of the above-mentioned highly acid-resistant and antioxidant probiotics in the preparation of products that regulate the balance of intestinal flora, wherein the highly acid-resistant and antioxidant probiotics are prepared by any of the methods described above, and the bacteria are probiotics.

[0043] Optionally, the probiotics are non-pathogenic Escherichia coli, Lactobacillus rhamnosus, Lactobacillus plantarum, Bifidobacterium longum, Bifidobacterium bifidum, and / or Bacillus subtilis.

[0044] Furthermore, the non-pathogenic Escherichia coli mentioned is Escherichia coli Nissle 1917.

[0045] This invention also claims protection for the use of the above-mentioned highly acid-resistant and antioxidant probiotics in the preparation of products for treating enteritis, wherein the highly acid-resistant and antioxidant probiotics are prepared by any of the methods described above, and the bacteria are probiotics.

[0046] Optionally, the probiotics are non-pathogenic Escherichia coli, Lactobacillus rhamnosus, Lactobacillus plantarum, Bifidobacterium longum, Bifidobacterium bifidum, and / or Bacillus subtilis.

[0047] Furthermore, the non-pathogenic Escherichia coli mentioned is Escherichia coli Nissle 1917.

[0048] The present invention has the following advantages and effects compared with the prior art: 1. The compound mineralized probiotics obtained by this invention not only improve the survival rate to nearly 90% under simulated gastric juice conditions, but also significantly reduce DPPH free radicals and ABTS free radicals, effectively improving the survival rate of probiotics in the gastrointestinal tract after oral delivery and enhancing the oral delivery therapy of probiotics.

[0049] 2. This invention does not simply involve physically mixing nanomaterials with bacteria, but rather involves in-situ synergistic mineralization on the bacterial surface to form a composite inorganic shell, resulting in a tighter interfacial bond and higher shell stability.

[0050] 3. This invention introduces cerium phosphate and cerium oxide together onto the surface of bacteria (probiotics) to achieve a dual-function synergy of "acid-resistant barrier + antioxidant scavenging"; compared with a single cerium phosphate layer or a single cerium oxide layer, it is more conducive to improving the viability of probiotics after they are transported through the gastrointestinal tract.

[0051] 4. The process conditions of this invention are mild and applicable to a variety of probiotic strains and different formulations, and have the potential for large-scale application.

[0052] 5. This invention presents a composite shell-enhanced probiotic system constructed based on an in-situ mineralization strategy. By effectively improving the gastrointestinal tolerance, in vivo survival rate, and colonization ability of probiotics, and endowing them with antioxidant properties, it significantly improves disease symptoms, inflammatory response, and intestinal microecological imbalance in UC mice. This provides important ideas and technical support for the development of novel probiotic delivery systems and the treatment research of inflammatory bowel disease. Attached Figure Description

[0053] Figure 1 The images shown are the results of transmission electron microscopy and energy dispersive spectroscopy (EDS) elemental scanning in Test Example 1; A is the result of transmission electron microscopy observation; B is the result of EDS elemental scanning of element C; C is the result of EDS elemental scanning of element Ce. Figure 2 The X-ray diffraction results are shown in Test Example 1. Figure 3 The image shows the X-ray photoelectron spectroscopy analysis results from Test Example 1; Figure 4 The graph shows the colon length measurements of mice in each group in test example 3; Figure 5 The graph shows the detection results of the inflammatory factor IL-1β in each group of mice in Test Example 3; Figure 6 The graph shows the detection results of the inflammatory factor IL-6 in each group of mice in Test Example 3; Figure 7 The graph shows the detection results of the inflammatory factor TNF-α in each group of mice in test example 3; Figure 8 This is a schematic diagram of the supernatant coated on plates at each dilution factor in Test Example 3; Figure 9 The images shown are: Plate observation diagrams of the plating method in Test Example 3; A is a plate observation diagram of the unmineralized group mice using the plating method; B is a plate observation diagram of the mineralized group mice using the plating method. Detailed Implementation

[0054] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto.

[0055] The Escherichia coli Nissle 1917 used in the embodiments of this invention was purchased from Sangon Biotech (Shanghai) Co., Ltd., platform number A330171-0001; Lactobacillus rhamnosus was purchased from Sangon Biotech (Shanghai) Co., Ltd., platform number A330720-0001; Lactobacillus plantarum was purchased from Sangon Biotech (Shanghai) Co., Ltd., platform number A340003-0001; Bifidobacterium longum was purchased from Sangon Biotech (Shanghai) Co., Ltd., platform number A340019-0001; Bifidobacterium bifidum was purchased from Sangon Biotech (Shanghai) Co., Ltd., platform number A331750-0001; Bacillus subtilis was purchased from Sangon Biotech (Shanghai) Co., Ltd., platform number A333118-0001.

[0056] The LB broth culture medium used in this embodiment of the invention was purchased from Guangdong Huankai Microbial Technology Co., Ltd., catalog number 028320.

[0057] Example 1: Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshells The preparation method is as follows: (1) Escherichia coli Nissle 1917 (ECN) was inoculated into LB broth medium and cultured at 37°C for 18 h. The bacterial cells were then collected by centrifugation, resuspended in PBS buffer, and the bacterial concentration was adjusted to 1×10⁻⁶. 9 CFU / mL; (2) Take 100 mL of bacterial solution (bacterial solution concentration is 1×10⁻⁶) 9 CFU / mL was added to bring the final concentration of cerium ions in the bacterial culture to 10 mmol / L, and the mixture was stirred for 20 min to adsorb. Then, sodium dihydrogen phosphate solution was added dropwise to bring the final concentration of phosphate in the bacterial culture to 20 mmol / L. The calculated ratio of the number of bacteria, the molar amount of cerium ions, and the molar amount of phosphate ions in the bacterial solution is 1×10⁻⁶. 11 CFU: 1 mmol: 2 mmol; (3) Adjust the pH of the system to 6.0 and react at 35℃ (reaction temperature) for 6 h (reaction time). After the reaction, centrifuge at 6000 rpm for 5 min and wash three times with physiological saline (0.9% NaCl) to obtain mineralized ECN probiotics with a composite nanoshell (containing cerium phosphate / cerium oxide) on the surface (referred to as sample 1).

[0058] Example 2: Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshells The difference from Example 1 is that in step (2), the ratio of the number of bacteria in the bacterial solution, the molar amount of cerium ions in the bacterial solution, and the molar amount of phosphate in the bacterial solution is 1×10. 9 CFU: 1 mmol: 0.1 mmol.

[0059] Everything else was exactly the same, and sample 2 was prepared.

[0060] Example 3: Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshells The difference from Example 1 is that in step (2), the ratio of the number of bacteria in the bacterial solution, the molar amount of cerium ions in the bacterial solution, and the molar amount of phosphate in the bacterial solution is 1×10. 10 CFU: 1 mmol: 0.5 mmol.

[0061] Everything else was exactly the same, and sample 3 was prepared.

[0062] Example 4: Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshells The difference from Example 1 is that in step (2), the ratio of the number of bacteria in the bacterial solution, the molar amount of cerium ions in the bacterial solution, and the molar amount of phosphate in the bacterial solution is 1×10. 12 CFU: 1 mmol: 5 mmol.

[0063] Everything else was exactly the same, and sample 4 was prepared.

[0064] Example 5: Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshells The difference from Example 1 is that in step (2), the ratio of the number of bacteria in the bacterial solution, the molar amount of cerium ions in the bacterial solution, and the molar amount of phosphate in the bacterial solution is 1×10. 13 CFU: 1 mmol: 10 mmol.

[0065] Everything else was exactly the same, and sample 5 was prepared.

[0066] Example 6 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (2), the bacterial concentration is 1×10⁻⁶. 7 CFU / mL.

[0067] Everything else was exactly the same, and sample 6 was prepared.

[0068] Example 7 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (2), the bacterial concentration is 1×10⁻⁶. 8 CFU / mL.

[0069] Everything else was exactly the same, and sample 7 was prepared.

[0070] Example 8 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (2), the bacterial concentration is 1×10⁻⁶. 10 CFU / mL.

[0071] Everything else was exactly the same, and sample 8 was prepared.

[0072] Example 9 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (2), the bacterial concentration is 1×10⁻⁶. 11 CFU / mL.

[0073] Everything else was exactly the same, and sample 9 was prepared.

[0074] Example 10 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (2), the final concentration of cerium ions is 0.1 mmol / L.

[0075] Everything else was exactly the same, and sample 10 was prepared.

[0076] Example 11 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (2), the final concentration of cerium ions is 1 mmol / L.

[0077] Everything else was exactly the same, and sample 11 was prepared.

[0078] Example 12 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (2), the final concentration of cerium ions is 30 mmol / L.

[0079] Everything else was exactly the same, and sample 12 was prepared.

[0080] Example 13 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (2), the final concentration of cerium ions is 100 mmol / L.

[0081] Everything else was exactly the same, and sample 13 was prepared.

[0082] Example 14 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (2), the final concentration of phosphate is 0.1 mmol / L.

[0083] Everything else was exactly the same, and sample 14 was prepared.

[0084] Example 15 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (2), the final concentration of phosphate is 1 mmol / L.

[0085] Everything else was exactly the same, and sample 15 was prepared.

[0086] Example 16 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (2), the final concentration of phosphate is 50 mmol / L.

[0087] Everything else was exactly the same, and sample 16 was prepared.

[0088] Example 17 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (2), the final concentration of phosphate is 100 mmol / L.

[0089] Everything else was exactly the same, and sample 17 was prepared.

[0090] Example 18 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (3), the pH of the system is adjusted to pH=3.5.

[0091] Everything else was exactly the same, and sample 18 was prepared.

[0092] Example 19 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (3), the pH of the system is adjusted to pH=4.5.

[0093] Everything else was exactly the same, and sample 19 was prepared.

[0094] Example 20 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (3), the pH of the system is adjusted to pH=7.5.

[0095] Everything else was exactly the same, and sample 20 was prepared.

[0096] Example 21 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (3), the pH of the system is adjusted to pH=9.0.

[0097] Everything else was exactly the same, and sample 21 was prepared.

[0098] Example 22 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (3), the reaction temperature is 10°C.

[0099] Everything else was exactly the same, and sample 22 was prepared.

[0100] Example 23 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (3), the reaction temperature is 20°C.

[0101] Everything else was exactly the same, and sample 23 was prepared.

[0102] Example 24 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (3), the reaction temperature is 45°C.

[0103] Everything else was exactly the same, and sample 24 was prepared.

[0104] Example 25 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (3), the reaction temperature is 60°C.

[0105] Everything else was exactly the same, and sample 25 was prepared.

[0106] Example 26 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (3), the reaction time is 0.5 h.

[0107] Everything else was exactly the same, and sample 26 was prepared.

[0108] Example 27 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (3), the reaction time is 1 h.

[0109] Everything else was exactly the same, and sample 27 was prepared.

[0110] Example 28 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (3), the reaction time is 12 h.

[0111] Everything else was exactly the same, and sample 28 was prepared.

[0112] Example 29 Preparation of mineralized ECN probiotics containing cerium phosphate / cerium oxide composite nanoshell The difference from Example 1 is that in step (3), the reaction time is 24 h.

[0113] Everything else was exactly the same, and sample 29 was prepared.

[0114] Example 30 Preparation of mineralized probiotics containing cerium phosphate / cerium oxide composite nanoshells The difference from Example 1 is that in step (1), Escherichia coli Nissle 1917 (ECN) is replaced with Lactobacillus rhamnosus.

[0115] Everything else was exactly the same, and sample 30 was prepared.

[0116] Example 31 Preparation of mineralized probiotics containing cerium phosphate / cerium oxide composite nanoshells The difference from Example 1 is that in step (1), Escherichia coli Nissle 1917 (ECN) is replaced with Lactobacillus plantarum.

[0117] Everything else was exactly the same, and sample 31 was prepared.

[0118] Example 32 Preparation of mineralized probiotics containing cerium phosphate / cerium oxide composite nanoshells The difference from Example 1 is that in step (1), Escherichia coli Nissle 1917 (ECN) is replaced with Bifidobacterium longum.

[0119] Everything else was exactly the same, and sample 32 was prepared.

[0120] Example 33 Preparation of mineralized probiotics containing cerium phosphate / cerium oxide composite nanoshells The difference from Example 1 is that in step (1), Escherichia coli Nissle 1917 (ECN) is replaced with Bifidobacterium bifidum.

[0121] Everything else was exactly the same, and sample 33 was prepared.

[0122] Example 34 Preparation of mineralized probiotics containing cerium phosphate / cerium oxide composite nanoshells The difference from Example 1 is that in step (1), Escherichia coli Nissle 1917 (ECN) is replaced with Bacillus subtilis.

[0123] Everything else was exactly the same, and sample 34 was prepared.

[0124] Comparative Example 1: Untreated ECN probiotics Escherichia coli Nissle 1917 was inoculated into LB broth medium and cultured at 37°C for 18 h. The bacterial cells were then collected by centrifugation, resuspended in PBS buffer, and the bacterial concentration was adjusted to 1×10⁻⁶. 9 CFU / mL was used to obtain ECN probiotic solution (referred to as sample 35).

[0125] Comparative Example 2: Mineralized ECN probiotics that only form a cerium phosphate shell Escherichia coli Nissle 1917 was inoculated into LB broth medium and cultured at 37°C for 18 h. The bacterial cells were then collected by centrifugation and resuspended in deoxygenated PBS buffer to adjust the bacterial concentration to 1×10⁻⁶. 9 CFU / mL.

[0126] Add deoxygenated cerium nitrate to 100 mL of bacterial culture to achieve a final cerium ion concentration of 10 mmol / L. Stir and adsorb under nitrogen protection for 20 min. Then, add deoxygenated sodium dihydrogen phosphate solution dropwise under nitrogen protection to achieve a cerium ion to phosphate molar ratio of 1:2. Adjust the pH of the system to 6.0 and react in a sealed environment at 35℃ for 6 h (the entire reaction is under nitrogen protection). After the reaction, centrifuge at 6000 rpm for 5 min and wash three times with physiological saline (0.9% NaCl) to obtain mineralized ECN probiotics that form only a cerium phosphate shell (referred to as sample 36).

[0127] Comparative Example 3: Mineralized ECN probiotics that only form a cerium oxide modified layer Escherichia coli Nissle 1917 was inoculated into LB broth medium and cultured at 37°C for 18 h. The bacterial cells were then collected by centrifugation, resuspended in PBS buffer, and the bacterial concentration was adjusted to 1×10^9 CFU / mL.

[0128] Cerium nitrate was added to 100 mL of bacterial culture to make the final concentration of cerium ions in the bacterial culture 10 mmol / L. The pH of the system was adjusted to 6.0, and the reaction was carried out at 35 °C for 6 h under aerobic stirring conditions. After the reaction was completed, the bacteria were centrifuged at 6000 rpm for 5 min and washed three times with physiological saline (0.9% NaCl) to obtain mineralized ECN probiotics with only a cerium oxide modified layer (referred to as sample 37).

[0129] Comparative Example 4: A physically mixed sample obtained by simply mixing pre-prepared cerium-containing nanomaterials with probiotics. Escherichia coli Nissle 1917 was inoculated into LB broth medium and cultured at 37°C for 18 h. The bacterial cells were then collected by centrifugation, resuspended in PBS buffer, and the bacterial concentration was adjusted to 1×10⁻⁶. 9 CFU / mL.

[0130] Cerium nitrate solution and sodium dihydrogen phosphate solution were mixed under sterile conditions to prepare a suspension of cerium phosphate / cerium oxide nanoparticles, wherein the final concentration of cerium ions in the suspension was 10 mmol / L and the final concentration of phosphate was 20 mmol / L. A suspension of *Escherichia coli* Nissle 1917 bacteria was mixed with the above suspension of cerium phosphate / cerium oxide nanoparticles at a volume ratio of 1:1. The mixture was incubated at 25°C for 30 min, centrifuged at 6000 rpm for 5 min, and washed once with physiological saline (0.9% NaCl) to obtain a physically mixed sample (referred to as sample 38).

[0131] Comparative Example 5 uses traditional organically encapsulated probiotic samples formed from polysaccharide or protein materials. Escherichia coli Nissle 1917 was inoculated into LB broth medium and cultured at 37°C for 18 h. The bacterial cells were then collected by centrifugation, resuspended in PBS buffer, and the bacterial concentration was adjusted to 1×10⁻⁶. 9 CFU / mL was used to obtain a suspension of Escherichia coli Nissle 1917.

[0132] Escherichia coli Nissle 1917 bacterial suspension was mixed with an equal volume of 2.0% (wt%) sodium alginate solution and added dropwise to 2.0% (wt%) calcium chloride solution to form gel microparticles. The microparticles were then coated with 0.5% (wt%) chitosan solution for 20 min and washed with physiological saline (0.9% NaCl) to obtain a traditional organically encapsulated probiotic sample (referred to as sample 39).

[0133] Test Example 1: Shell Structure Characterization The mineralized ECN probiotics obtained in Example 1 (sample 1) were observed by transmission electron microscopy and elemental spectroscopy (for C and Ce elements); the mineralized ECN probiotics obtained in Example 1 (sample 1) and Escherichia coli Nissle 1917 (ECN, unmineralized, sample 35 of Comparative Example 1) were subjected to X-ray diffraction; the mineralized ECN probiotics obtained in Example 1 (sample 1) and the mineralized ECN probiotics that only formed a cerium oxide modified layer (sample 37 of Comparative Example 3) were subjected to X-ray photoelectron spectroscopy analysis.

[0134] The results of transmission electron microscopy and energy-dispersive elemental scanning are shown in the figure. Figure 1 As shown, Figure 1 In the image, A represents the result of transmission electron microscopy. Figure 1 In the image, B represents the elemental energy spectrum scan result of element C. Figure 1 The C in the figure represents the elemental energy dispersive spectroscopy (EDS) results for Ce. The results show that a continuous nanoshell was formed on the surface of the mineralized ECN probiotics, with an average particle size of 30–90 nm and an average thickness of 15–45 nm. The X-ray diffraction (XRD) results are shown in the figure. Figure 2 As shown in the figure, the X-ray photoelectron spectroscopy (XPS) analysis results are as follows: Figure 3 As shown, the results indicate that the mineralized ECN probiotics (sample 1) with a surface-formed composite nanoshell (containing cerium phosphate / cerium oxide) prepared in Example 1 simultaneously exhibit characteristic signals of both cerium phosphate and cerium oxide. Furthermore, compared to the mineralized ECN probiotics (sample 37) in Comparative Example 3 which only formed a cerium oxide modification layer, the introduction of cerium phosphate increased the Ce content. 3+ The proportions enhanced Ce 3+ / Ce 4+ The redox cycle.

[0135] Test Example 2: Acid Resistance and Antioxidant Performance Test Methods I. Experimental Methods 1. Acid resistance test method The samples prepared in Examples 1-17, Examples 30-34, and Comparative Examples 1-5, as well as the unmineralized control bacterial solutions (including *Escherichia coli* Nissle 1917, *Lactobacillus rhamnosus*, *Lactobacillus plantarum*, *Bifidobacterium longum*, *Bifidobacterium bifidum*, and *Bacillus subtilis*), were diluted with physiological saline (0.9% NaCl) and added to centrifuge tubes containing simulated gastric juice (pH=2.0), so that the initial bacterial count in the centrifuge tubes was 1×10⁻⁶. 9 CFU was incubated at 37℃ for 2 hours. After the culture was completed, the sample was centrifuged at 6000 rpm for 5 minutes. The precipitate was collected and washed once with physiological saline (0.9% NaCl). The survival rate of acid resistance test was calculated by plate counting method. Three parallel experiments were set up for each sample. The results are expressed as mean ± standard deviation.

[0136] 2. Antioxidant performance test method The antioxidant capacity of each sample was evaluated using DPPH and ABTS free radical scavenging assays, as detailed below: The bacterial concentrations of the samples obtained in Examples 1-34 and Comparative Examples 1-5, as well as the unmineralized control bacterial solutions (including Escherichia coli Nissle 1917, Lactobacillus rhamnosus, Lactobacillus plantarum, Bifidobacterium longum, Bifidobacterium bifidum, and Bacillus subtilis), were adjusted to 1×10⁻⁶ using physiological saline (0.9% NaCl). 9CFU / mL was used to obtain the bacterial suspensions of each sample, and DPPH free radical scavenging and ABTS free radical scavenging experiments were performed; among them, the samples of Examples 30 to 34 were only subjected to the DPPH free radical scavenging rate experiment.

[0137] DPPH free radical scavenging experiment: The DPPH free radical scavenging capacity test kit (Beijing Solarbio Science & Technology Co., Ltd., BC4750) was used to test the DPPH free radical scavenging rate of the samples according to the kit instructions, and the DPPH free radical scavenging rate of each sample was recorded.

[0138] ABTS free radical scavenging assay: The total antioxidant capacity assay kit (ABTS method) (Shanghai Beyotime Biotechnology Co., Ltd., S0119) was used to test the ABTS free radical scavenging rate of the samples according to the kit instructions, and the ABTS free radical scavenging rate of each sample was recorded.

[0139] II. Experimental Results The acid resistance and antioxidant properties of the samples prepared in Examples 1-34 and Comparative Examples 1-5 are as follows: 1. Comparison of acid resistance test survival rate results of samples from Example 1 and Comparative Examples 1-5 The acid resistance test survival rate results of the samples of Example 1 and Comparative Examples 1-5 are shown in Table 1.

[0140] Table 1. Acid resistance test survival rate results of samples from Example 1 and Comparative Examples 1-5

[0141] The results showed that the survival rate of the mineralized ECN probiotics (i.e., sample 1) with a surface composite nanoshell (containing cerium phosphate / cerium oxide) prepared in Example 1 reached 85.7% ± 2.3% after incubation in simulated gastric juice for 2 hours, which was significantly better than the survival rate of the samples prepared in Comparative Examples 1 to 5. This indicates that sample 1 prepared in Example 1 forms an acid-resistant barrier after the in-situ formation of a cerium phosphate / cerium oxide composite nanoshell on the surface of the probiotic (ECN), and has excellent acid resistance.

[0142] 2. Comparison of antioxidant performance test results between Example 1 and Comparative Examples 1-5 The antioxidant performance test results of the samples from Example 1 and Comparative Examples 1-5 are shown in Table 2.

[0143] Table 2. Antioxidant performance test results of samples from Example 1 and Comparative Examples 1-5

[0144] The results showed that the mineralized ECN probiotics with a surface-formed composite nanoshell (containing cerium phosphate / cerium oxide) prepared in Example 1 (i.e., Sample 1) had a DPPH radical scavenging rate of 78.9% ± 2.1% and an ABTS radical scavenging rate of 79.1% ± 2.0%, indicating that Sample 1 prepared in Example 1 has excellent antioxidant properties. In contrast, the DPPH radical scavenging rate and ABTS radical scavenging rate of the samples prepared in Comparative Examples 1 to 5 all decreased significantly, indicating that only by following the method shown in Example 1 can probiotics (ECN) with excellent antioxidant properties be prepared.

[0145] 3. Effects of different bacterial, cerium ion, and phosphate ratios on mineralization efficiency The results of acid resistance and antioxidant performance tests of the samples in Examples 1 to 5 are shown in Table 3.

[0146] Table 3 Test results of samples from Examples 1 to 5

[0147] The results showed that the ratio of the number of bacteria, the molar amount of cerium ions, and the molar amount of phosphate ions in the bacterial solution was within 1×10⁻⁶. 9 ~1×10 13 When the CFU concentration is within the range of 0.1–10 mmol, the prepared samples all exhibit certain acid resistance and antioxidant properties. They can all form a cerium phosphate / cerium oxide composite nanoshell on the surface of probiotic (ECN) cells, thereby enhancing acid resistance and antioxidant properties. Specifically, when the ratio of the number of bacteria, the molar amount of cerium ions, and the molar amount of phosphate in the bacterial solution is 1 × 10⁻⁶, the results are particularly effective. 11 When the CFU ratio is 1 mmol: 2 mmol (i.e., the scheme shown in Example 1), the cerium phosphate / cerium oxide composite nanoshell formed on the surface of the bacteria is relatively uniform, and the overall acid resistance and antioxidant properties are optimal.

[0148] 4. Effect of different bacterial solution concentrations on mineralization effect The test results of acid resistance and antioxidant properties of the samples in Examples 1 and 6-9 are shown in Table 4.

[0149] Table 4. Test results of acid resistance and antioxidant properties of samples from Examples 1 and 6-9.

[0150] The results showed that the concentration of the bacterial culture was 1×10⁻⁶. 7 ~1×10 11 Mineralizing bacteria can be obtained within the CFU / mL range, and they also exhibit excellent acid resistance and antioxidant properties; when the bacterial concentration is too low (1×10⁻⁶), 7CFU / mL), the deposition on the surface of the bacterial cells is relatively sufficient, but the overall recovery is low. When the bacterial concentration is too high (1×10), the recovery rate is even lower. 11 CFU / mL), shell homogeneity decreased slightly; bacterial concentration was 1×10⁻⁶. 8 ~1×10 10 The overall performance is better within the CFU / mL range, with a bacterial concentration of 1×10⁻⁶. 9 At a concentration of CFU / mL (i.e., the scheme shown in Example 1), the mineralized ECN probiotics with a cerium phosphate / cerium oxide composite nanoshell prepared exhibit the best acid resistance and antioxidant properties.

[0151] 5. Effect of different final cerium ion concentrations on mineralization effect The test results of acid resistance and antioxidant properties of the samples from Examples 1 and Examples 10-13 are shown in Table 5.

[0152] Table 5. Test results of acid resistance and antioxidant properties of samples from Examples 1 and Examples 10-13.

[0153] The results showed that when the final concentration of cerium ions in the bacterial solution prepared by the method shown in Example 1 was adjusted to 0.1 mmol / L to 100 mmol / L, mineralized probiotics containing a cerium composite mineralization layer (i.e., a cerium phosphate / cerium oxide composite nanoshell) could be formed. When the final concentration of cerium ions was too low (0.1 mmol / L), the shell formed was thinner and had poor acid resistance and antioxidant properties. When the final concentration of cerium ions was too high (100 mmol / L), the shell formed was thicker and also affected the activity of probiotics, resulting in a decrease in the survival rate of probiotics.

[0154] Therefore, when the final concentration of cerium ions in the bacterial solution is between 1 mmol / L and 30 mmol / L, the prepared mineralized ECN probiotics have better acid resistance and antioxidant properties, and the performance is optimal when the final concentration of cerium ions in the bacterial solution is 10 mmol / L.

[0155] 6. Effect of different final phosphate concentrations on mineralization effect The test results of acid resistance and antioxidant properties of the samples in Examples 1 and Examples 14-17 are shown in Table 6.

[0156] Table 6. Acid resistance and antioxidant properties of samples from Examples 1 and Examples 14-17

[0157] The results showed that when the final concentration of phosphate in the bacterial solution prepared by the method shown in Example 1 was adjusted to 0.1 mmol / L to 100 mmol / L, mineralized probiotics containing a cerium-containing composite mineralization layer (i.e., a cerium phosphate / cerium oxide composite nanoshell) could be formed, exhibiting certain acid resistance and antioxidant properties. When the phosphate concentration in the bacterial solution was too low (0.1 mmol / L), the cerium phosphate barrier in the composite nanoshell was insufficient, resulting in lower acid resistance and antioxidant properties. When the phosphate concentration in the bacterial solution was too high (100 mmol / L), the uniformity of the composite nanoshell decreased, and the acid resistance and antioxidant properties also decreased to some extent.

[0158] When the final phosphate concentration in the bacterial solution is between 1 mmol / L and 100 mmol / L, the prepared mineralized ECN probiotics exhibit superior acid resistance and antioxidant properties, with the best performance observed when the final phosphate concentration in the bacterial solution is 20 mmol / L.

[0159] 7. Effects of different pH conditions on mineralization The antioxidant performance test results of the samples from Examples 1 and 18-21 are shown in Table 7.

[0160] Table 7. Antioxidant performance test results of samples from Examples 1 and 18-21

[0161] The results showed that adjusting the pH of the system to the range of 3.5 to 9.0 could form a cerium phosphate / cerium oxide composite shell and improve the antioxidant properties of probiotics. The products prepared with a pH of 4.5 to 7.5 had better effects, and the products prepared with a pH of 6.0 had the best effects.

[0162] 8. The effect of different temperature conditions on mineralization effect The antioxidant performance test results of the samples from Examples 1 and 22-25 are shown in Table 8.

[0163] Table 8. Antioxidant performance test results of samples from Examples 1 and 22-25.

[0164] The results showed that, as shown in Example 1, adjusting the reaction temperature to 10℃~60℃ could form a cerium phosphate / cerium oxide composite shell and improve the antioxidant properties of probiotics; among them, the product prepared at a reaction temperature of 20℃~45℃ had better effects, and the product prepared at a reaction temperature of 35℃ had the best effects.

[0165] 9. Effect of different reaction times on mineralization effect The antioxidant performance test results of the samples in Examples 1 and 26-29 are shown in Table 9.

[0166] Table 9. Antioxidant performance test results of samples from Examples 1 and 26-29.

[0167] The results showed that, as shown in Example 1, adjusting the reaction temperature to 0.5h to 24h could form a cerium phosphate / cerium oxide composite shell and improve the antioxidant properties of probiotics; among them, the product prepared in the reaction time range of 6h to 24h had better effects, and the product prepared in the reaction time of 6h had the best effects.

[0168] 10. Compatibility verification of different probiotic strains The acid resistance and DPPH free radical scavenging rate test results of the samples in Example 1 and Examples 30-34 are shown in Table 10.

[0169] Table 10. Test results of acid resistance and DPPH free radical scavenging rate of samples from Examples 1 and Examples 30-34.

[0170] The results showed that mineralization treatment of probiotics (including non-pathogenic Escherichia coli, Lactobacillus rhamnosus, Lactobacillus plantarum, Bifidobacterium longum, Bifidobacterium bifidum, and Bacillus subtilis) could produce mineralized probiotics with a composite nanoshell (containing cerium phosphate / cerium oxide) on their surface. Compared with the original probiotics, the acid resistance (survival rate) and antioxidant properties of the mineralized probiotics were significantly improved.

[0171] Test Example 3: Validation of the ability to treat a colitis model I. Experimental Methods Five- to six-week-old male Balb / c mice were randomly divided into four groups (n = 4) after 7 days of acclimatization feeding: healthy group, model group, unmineralized group, and mineralized group.

[0172] After the adaptive feeding period, healthy mice were given ordinary drinking water throughout the entire period, while the other three groups were given drinking water containing 3% sodium dextran sulfate (wt%) for 5 days to induce an enteritis model. After the induction was completed, mice in each group were administered the drug by gavage.

[0173] The mice in each group were administered the following via gavage: Healthy group: administered 200 µL of ordinary drinking water by gavage; Model group: 200 µL of 1×PBS buffer was administered by gavage; Unmineralized group: Administered 200 µL of unmineralized probiotics by gavage (200 μL contains 1 × 10⁻⁶ bacteria). 9CFU); Mineralized group: Administered 200 µL of mineralized probiotics by gavage (200 μL contains 1 × 10⁻⁶ bacteria). 9 CFU); Mice in each group were treated by gavage for 5 consecutive days, once a day. The unmineralized probiotics were Escherichia coli Nissle1917 (purchased from Sangon Biotech (Shanghai) Co., Ltd., platform number A330171-0001), and the mineralized probiotics were mineralized ECN probiotics prepared according to Example 1. Both the unmineralized and mineralized probiotics were diluted to the corresponding concentrations with physiological saline.

[0174] After gavage treatment, blood was collected from each group of mice, and serum was collected from each group of mice after centrifugation. Enzyme-linked immunosorbent assay (ELISA) was used to detect the levels of interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) in the serum of mice in each group of mice according to the instructions of the kits, using a mouse tumor necrosis factor-α (TNF-α) kit (purchased from Shanghai Yuanju Biotechnology Center, YJ002095), a mouse interleukin-6 (IL-6) ELISA kit (purchased from Shanghai Yuanju Biotechnology Center, YJ098430), and a mouse interleukin-1β (IL-1β) ELISA kit (purchased from Shanghai Yuanju Biotechnology Center, YJ696735).

[0175] Next, the cecum and colon of each group of mice were removed and separated, and the colon length of each group of mice was measured. Next, the cecum and colon of mice in both the unmineralized and mineralized groups were homogenized using 1×PBS buffer. After homogenization, the supernatant from the cecum and colon of both groups was collected and processed according to a 5×10⁻⁶ ppm standard. 8 5×10 7 5×10 6 5×10 5 5×10 4 and 5×10 3 The mice were serially diluted, and the number of viable bacteria in the cecum and colon of both groups of mice was determined by the plating method for the supernatant of each serial dilution.

[0176] II. Experimental Results The colon length measurements of each group of mice are shown in the figure below. Figure 4 As shown, the results indicated that the colon length of the mice in the model group was significantly shorter than that in the healthy group, indicating that the enteritis model was successfully established. After gavage treatment, the colon length of mice in both the unmineralized and mineralized groups recovered to varying degrees. The colon length of mice in the mineralized group was significantly higher than that in the model group, and the effect was better than that in the unmineralized group.

[0177] The results of the detection of the inflammatory factor IL-1β in each group of mice are shown in the figure below. Figure 5 As shown in the figure, the detection results of the inflammatory factor IL-6 in each group of mice are as follows. Figure 6 As shown in the figure, the detection results of the inflammatory factor TNF-α in each group of mice are as follows. Figure 7 As shown in the figure (** indicates P<0.01, *** indicates P<0.001, **** indicates P<0.0001); the results showed that compared with the healthy group, the levels of three pro-inflammatory cytokines in the serum of mice in the model group were increased, indicating that the inflammatory response in the enteritis model mice was severe. After gavage treatment, the levels of pro-inflammatory cytokines in the serum of mice in both the unmineralized and mineralized groups decreased to varying degrees. The levels of pro-inflammatory cytokines in the mineralized group were significantly better than those in the unmineralized group, and the levels of IL-1β, IL-6, and TNF-α were significantly lower than those in the model group, while there was no significant difference in levels compared with the healthy group. This indicates that the mineralized probiotics have excellent therapeutic effects in alleviating inflammation in the enteritis model mice.

[0178] Schematic diagrams of the supernatant spread plates at each dilution factor are shown below. Figure 8 As shown; a plate observation diagram of the coating plate method is shown below. Figure 9 As shown, Figure 9 In the image, A represents the plate observation diagram of the unmineralized group mice using the plating method. Figure 9 B in the figure is a plate observation diagram of the mineralized group mice using the plate method.

[0179] The results showed that the total number of viable bacteria in the cecum and colon of the mineralized group was 163,850,005 ± 27,950,002 CFU, while that in the unmineralized group was 14,252,342 ± 2,367,319 CFU. The number of viable bacteria in the mineralized group was 11.5 times that in the unmineralized group, indicating that the survival ability of mineralized probiotics in the cecum and colon was superior to that of unmineralized probiotics.

[0180] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for synergistic mineralizing bacteria of cerium phosphate and cerium oxide, comprising the following steps: S1. Add cerium ions and phosphate to the bacterial culture; The bacterial solution is a probiotic solution; the concentration of the bacterial solution is 1×10⁻⁶. 7 ~1×10 11 CFU / mL; the final concentration of cerium ions in the bacterial solution is 1–30 mmol / L; the final concentration of phosphate ions in the bacterial solution is 1–100 mmol / L; S2. The reaction is carried out at a pH of 3.5–9.0 and a temperature of 10–60℃ for 0.5–24 h to obtain the mineralized bacterial solution after reaction and mineralization.

2. The method according to claim 1, characterized in that, The addition of cerium ions and phosphate as described in S1 is as follows: first add the reagent containing cerium ions, stir and adsorb for 5 to 60 minutes, and then add the reagent containing phosphate. The cerium-containing reagents include soluble cerium salts; The phosphate-containing reagents include at least one of soluble inorganic phosphates and soluble organic phosphates.

3. The method according to claim 1, characterized in that, The ratio of bacteria, cerium ions, and phosphate in the bacterial solution described in S1 is 1×10⁻⁶. 11 ~1×10 13 CFU: 1 mmol: 2-5 mmol.

4. A cerium phosphate-oxidizing synergistic mineralizing bacterium, characterized in that, The mineralizing bacteria are prepared by the method of cerium phosphate and cerium oxide synergistic mineralizing bacteria as described in any one of claims 1 to 3, and the mineralizing bacteria have high acid resistance and antioxidant effect.

Citation Information

Patent Citations

  • Preparation method of biomineralized coated bacteria, biomineralized coated bacteria and application of biomineralized coated bacteria

    CN115927284A

  • Nanometer enzyme coating modified probiotics as well as preparation method and application thereof

    CN121265652A